2018
DOI: 10.1002/dneu.22639
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Synaptic Bases of CDKL5 Disorder

Abstract: The X‐linked gene cyclin‐dependent kinase‐like 5 (CDKL5) encodes a serine/threonine kinase abundantly expressed in the brain. Mutations in CDKL5 have been associated with neurodevelopmental disorders characterized by early‐onset epileptic encephalopathy and severe intellectual disability, suggesting that CDKL5 plays important roles in brain development and function. Recent studies using cultured neurons, knockout mice, and human iPSC‐derived neurons have demonstrated that CDKL5 regulates axon outgrowth, dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 79 publications
0
59
0
Order By: Relevance
“…[24][25][26][27] The CDKL5 protein has roles in cell proliferation, neuronal migration, axonal outgrowth, dendritic morphogenesis and synapse development and function in the adult brain. 28 CDKL5 has multiple transcripts due to alternative splicing in mice and humans. The primary brain isoform is hCDKL5_1.…”
Section: Cdkl5 Protein and Molecular Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27] The CDKL5 protein has roles in cell proliferation, neuronal migration, axonal outgrowth, dendritic morphogenesis and synapse development and function in the adult brain. 28 CDKL5 has multiple transcripts due to alternative splicing in mice and humans. The primary brain isoform is hCDKL5_1.…”
Section: Cdkl5 Protein and Molecular Biologymentioning
confidence: 99%
“…Molecular studies in rodent models have identified several pathways are altered in CDD, including the AKT/mTOR, AKT/GSK-3b and BDNF-Rac1 signaling pathways and the NGL-1-PSD95 interaction. 24,25,27,28,40,41 However, these rodent models demonstrate a behavioral phenotype but lack spontaneous seizure activity. [41][42][43] Dendritic outgrowth and spine development are inconsistently altered in cellular CDD models.…”
Section: Cdkl5 Protein and Molecular Biologymentioning
confidence: 99%
“…CDKL5 protein is widely expressed in the brain and plays important roles in cell proliferation, neuronal migration, axonal outgrowth, dendritic morphogenesis, and synapse development [7,8]. Typical clinical characters of CDKL5-related disorders (CDD) include infantile-onset refractory epilepsy, hypotonia, developmental delay, intellectual disability, and visual impairment [2][3][4]9].…”
Section: Discussionmentioning
confidence: 99%
“…So far more than 100 pathogenic mutations have been reported. The clinical severity is associated with the location and type of mutations; for example, missense mutations located in the catalytic domain of CDKL5 could exhibit more severe phenotypes compared to patients carrying other CDKL5 mutations [8], but the exact genotype-phenotype correlation still remains obscure. In our patients, the three mutations are all de novo, as no mutations were found in their parents, and there were no reports previously.…”
Section: Discussionmentioning
confidence: 99%
“…The highest expression levels are in the peri- and postnatal stages of the nervous system, suggesting an important role in the process of brain development [ 23 ]. Recent studies demonstrated that CDKL5 regulates axon outgrowth, dendritic morphogenesis and synapse formation [ 24 ]. The first identified EIEE-causing gene was ARX , encoding the transcription factor Aristaless-Related Homeobox [ 25 ].…”
Section: Developmental and Epileptic Encephalopathy (Dee)mentioning
confidence: 99%